Portaria PGR/MPF nº 541, de 13 de junho de 2018 - Raquel Elias Ferreira Dodge (DOU, Brasília, DF, 21 jun. 2018. Seção 2, p. 45., 2018)
Altera o art. 2º da Portaria PGR/MPF nº 316, de 10 de abril de 2018.